First report of Corynespora cassiicola causing leaf spot on Begonia fimbristipula in China - Xiaobo Zhang; Xiaoyi Zuo; Jianhua Lu; Ya Xiao; Yuanshun Wang; Huan Chen; Yuting Zhang; Xun Lu (PLoS ONE, 2026)
Background Begonia fimbristipula , an economically important medicinal plant in southern China, has recently suffered severe yield losses from leaf spot disease in Guizhou and Hunan Provinces; the causal pathogen remains unknown. Methods Field surveys were conducted across multiple locations in Guizhou and Hunan Provinces to record disease symptoms and incidence. The pathogen was isolated from diseased leaves via tissue culture, and identified by combining morphological characteristics and multilocus phylogenetic analysis (ITS, TEF1α, RPB2). Pathogenicity was verified by fulfilling Koch’s postulates through artificial inoculation and re-isolation assays. Results Severe leaf spot outbreaks were observed in August 2024, with over 60% disease incidence across 667 hectares and >20% fresh leaf yield loss. The isolated pathogen was identified as Corynespora cassiicola based on gray to dark-gray colonies, pale-brown olivaceous conidia with 0–15 pseudosepta, and ≥98% bootstrap support in phylogenetic clustering with known C. cassiicola strains. Koch's postulates were fulfilled by reproducing typical field symptoms on inoculated B. fimbristipula seedlings and re-isolating the pathogen. Conclusions This is the first report of C. cassiicola causing leaf spot on B. fimbristipula in China, expanding the host range of this pathogen. Our findings provide a critical basis for the accurate diagnosis of this newly emerging disease on the medicinal plant.